2018
DOI: 10.15516/cje.v20i4.3001
|View full text |Cite
|
Sign up to set email alerts
|

Media and Information Literacy - the Basis for Applying Digital Technologies in Teaching from the Discourse of Educational Needs of Teachers / Medijska i informacijska pismenost – osnova za primjenu digitalnih tehnologija u nastavi iz diskursa obrazovnih

Abstract: The expansion of new digital media and the development of information technology give even bigger importance to media and information literacy, which is recognized as one of the key skills in the educational system almost everywhere in the world. The concept of media and information literacy in this paper is considered from the pedagogical aspect, i.e., the aspect of the educational needs of the teacher in learning and applying digital technologies in the teaching process.The aim of this paper is to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 2 publications
1
6
0
1
Order By: Relevance
“…The intimacy which refers to the teacher's depth in mastering digital technology, will certainly strengthen the teacher's confidence and trust in his teaching ability. This is also evidenced by previous relevant research which revealed that the intimacy of digital technology plays a very important role in online learning that requires a comprehensive integration of digital technology [57]- [59].…”
Section: Discussionsupporting
confidence: 56%
“…The intimacy which refers to the teacher's depth in mastering digital technology, will certainly strengthen the teacher's confidence and trust in his teaching ability. This is also evidenced by previous relevant research which revealed that the intimacy of digital technology plays a very important role in online learning that requires a comprehensive integration of digital technology [57]- [59].…”
Section: Discussionsupporting
confidence: 56%
“…This is a relatively new form of behavioural addiction associated with risky behaviours in the area of cyberspace, television and mobile phones. As a result of relationships now being mediated by different technologies, the population affected by compulsive media use is growing (Macuch et al, 2018;Novković Cvetković, Stošić, & Belousova, 2018;Ogonowska, 2014).…”
mentioning
confidence: 99%
“…However, a number of scholars pay attention to the fact that along with the prospects for digitalization of higher pedagogical education, there are also risk factors for the formation of students' innovative thinking [11][12][13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%